Sedum xunvense, a new species from Southeast China - Chai, Mao-Lin; Wu, Ya-Meng; Zhang, Yang; Pu, Jin-Bao; Chen, Bin; Xu, Yue-Liang; Li, Pan (Phytotaxa, 2024)
In this paper, Sedum xunvense is described as a new species from Zhejiang, Southeast China. Sedum xunvense is morphologically similar to S. formosanum, but the latter differs in clustered and robust stems (vs. solitary, slender), green or slightly red smooth stems and inflorescence rachises (vs. purple-red and ribbed), thick and succulent leaves (vs. thin), yellow anthers (vs. reddish-brown), erect follicles (vs. oblique), and is found in dry habitats in rock crevices (vs. damp ravines, rocks and mossy thickets). A reconstructed ML phylogeny of Sedum, based on nrITS sequence data, strongly suggests that S. xunvense forms an independent clade that is sister to a larger clade of many species, including S. formosanum.